PENGARUH MODEL PEMBELAJARAN LISTENING TEAM TERHADAP SIKAP PERCAYA DIRI DAN KERJASAMA SISWA PADA PEMBELAJARAN PPKn KELAS IX SMP NEGERI 1 TRAGAH - Yusuf, Yunizar An Natsirul; Huda, Nuril; Utami, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of the research refers to the problem formulation as follows: 1) To determine the influence of the listening team model on students' self-confident attitudes in PPKn learning class IX SMP Negeri 1 Tragah, and 2) To determine the effect of the listening team model on student collaboration in PPKn learning class IX SMP Negeri 1 Tragah. Researchers tested the use of the learning team learning model in Civics learning and found out its effect on students' self-confidence and cooperation. Based on these activities, the research carried out by the researcher is experimental research and is a type of research in quantitative research. The researcher chose one of the experimental research designs from quasi experimental design, namely Nonequivalent Control Group Design. The research samples were 30 students in class IX-A as the control class and 30 students in class IX-B as the experimental class. Researchers develop research instruments that will be used as research data collection tools. There were two research instruments developed, namely a self-confidence questionnaire sheet and a collaboration questionnaire sheet. Data analysis used the independent sample t test analysis technique. The research conclusions are: 1) There is an influence of the listening team model on students' self-confident attitudes in PPKn learning class IX SMP Negeri 1 Tragah, and 2) There is an influence of the listening team model on student cooperation in PPKn learning class IX SMP Negeri 1 Tragah.